Naringin improves sepsis-induced intestinal injury by modulating macrophage polarization via PPARγ/miR-21 axis - Zhi-Ling Li; Bing-Chang Yang; Ming Gao; Xue-Fei Xiao; Shang-Ping Zhao; Zuo-Liang Liu (Elsevier, 2021)
Naringin exhibited various pharmacological activities. However, its biological function and underlying mechanism in regulating macrophage polarization remain elusive. This study aimed to investigate the regulatory network between naringin and macrophage polarization in sepsis-induced intestinal injury. Cecal ligation and puncture (CLP) was used to establish the animal model of sepsis. Chromatin immunoprecipitation and a luciferase reporter assay were used to determine the interplay between peroxisome proliferator-activated receptor γ (PPARγ) and miR-21 promoter, as well as miR-21 and its target genes. Naringin enhanced the overall survival of septic mice and alleviated the CLP-induced inflammatory response and intestinal damage. This was accompanied by the increased expression of PPARγ in the intestines and the stimulation of ileal macrophages toward the M2 phenotype. Furthermore, in lipopolysaccharide-stimulated bone marrow-derived macrophages, naringin stimulated M2 polarization. Mechanistically, PPARγ inhibition attenuated the promotion of M2 polarization caused by naringin, and the naringin/PPARγ regulatory work was compromised by miR-21 inhibition. The present study suggested that naringin promoted M2 polarization via the PPARγ/miR-21 axis, thus relieving sepsis-induced intestinal injury. This study provides novel insights into the mechanism by which naringin alleviated sepsis-induced intestinal injury through regulation of macrophage polarization.